Genome-wide Identification and Characterization of the GRAS Transcription Factors in Garlic (Allium sativum L.) - Zhang, Xueyu; Yang, Xiai; He, Qiaoyun; Wang, Yanzhou; Liang, Guolu; Liu, Touming (Frontiers in Plant Science, 2022)
GRAS transcription factors play crucial roles in plant growth and development and have been widely explored in many plant species. Garlic (Allium sativum L.) is an important crop owing to its edible and medicinal properties. However, no GRAS transcription factors have been identified in this crop. In this study, 46 garlic GRAS genes were identified and assigned to 16 subfamilies using the GRAS members of Arabidopsis thaliana, Oryza sativa, and Amborella trichopoda as reference queries. Expression analysis revealed that garlic GRAS genes showed distinct differences in various garlic tissues, as well as during different growth stages of the bulbs. Five of these 46 genes were identified as DELLA-like protein-encoding genes and three of which, Asa2G00237.1/Asa2G00240.1 and Asa4G02090.1, responded to exogenous GA3 treatment, and showed a significant association between their transcription abundance and bulb traits in 102 garlic accessions, thereby indicating their role in regulating the growth of garlic bulbs. These results will lay a useful foundation for further investigation of the biological functions of GRAS genes and guiding the genetic breeding of garlic in the future.